Cenozoic Antarctic climate evolution based on molecular and isotopic biomarker reconstructions from geological archives in the Ross Sea region - Bella Duncan (8511405) (2017)
During the Cenozoic Era (the last 65 Ma), Antarctica’s climate has evolved from ice free conditions of the ‘Greenhouse world’, which at its peak (~ 55 Ma) supported near-tropical forests, to the ‘Icehouse’ climate of today with permanent ice sheets, and a very sparse macroflora. This long-term cooling trend is punctuated by a number of major, abrupt, and in some cases, irreversible climate transitions. Reconstructing past changes in vegetation, sea surface temperature, hydroclimate and the carbon cycle require robust geological proxies that in turn can provide insights into climatic thresholds and feedbacks that drove major transitions in the evolution of Antarctica’s ice sheets. Biomarkers allow climate and environmental proxy reconstructions for this region, where other more traditional paleoclimate methods are less suitable. This study has two aims. Firstly to assess the suitability and applicability of biomarkers in Antarctic sediments across a range of depositional settings and ages, and secondly to apply biomarker-based climate proxies to reconstruct environmental and climate conditions during key periods in the development of the Antarctic Ice Sheets. The distribution and abundances of n-alkanes are assessed in Oligocene and Miocene sediments from a terrestrial outcrop locality in the Transantarctic Mountains, and two glaciomarine sediment cores and an ice-distal deep marine core from the western Ross Sea. Comparisons are made with n-alkane distributions in Eocene glacial erratics and sedimentary rocks of the Mesozoic Beacon Supergroup, both likely sources of reworked material. A shift in dominant chain length from n-C₂₉ to n-C₂₇ occurs between the Late Eocene and Early Oligocene, considered a response to a significant climate cooling. Samples from glaciofluvial environments onshore, and subglacial and ice-proximal environments offshore display a reworked n-alkane distribution, characterised by low carbon preference index (CPI), high average chain length (ACL) and high n-C₂₉/n-C₂₇ values. Whereas, samples from lower-energy, more benign lacustrine and ice-distal marine environments predominantly contained contemporary material. Palynomorphs and biomarker proxies based on n-alkanes and glycerol dialkyl glycerol tetraethers (GDGTs) are applied to a Late Oligocene and Early Miocene glaciomarine succession spanning the large transient excursion of the Mi-1 glaciation (~23 Ma) in DSDP Site 270 drill core from the central Ross Sea. While the Late Oligocene is marked by relatively warm conditions, regional cooling initiated a transition into Mi-1. This was likely driven by a combination of decreasing atmospheric CO₂ and an orbital geometry favouring low seasonality and cool summers, leading to an intensification of proto-Antarctic bottom water production as the Ross Sea deepened and cooled. Mi-1 manifests as a regionally cool period, with minimum subsurface temperatures of ~4°C and onshore mean summer temperatures of ~8°C. A negative n-alkane δ¹³C excursion of up to 4.8‰ is interpreted as a vegetation response to cold, restricted growing seasons, with plants driven to lower altitudes and more stunted growth forms. However, ocean temperatures remained too warm for marine-based ice sheets to advance onto the outer continental shelf and over-ride the drill site. The large increase in ice volume associated with this event, implied by global δ¹⁸O records, was probably held on a higher, terrestrial West Antarctica of greater extent than present day. The relative lack of ice rafted debris during Mi-1, suggests the presence of a marginal marine-terminating ice sheet with fringing ice shelves to the south of DSDP site 270, calving icebergs lacking a basal debris layer, similar to those calving from the Ross Ice Shelf today. This extensive ice cover may explain a large decrease in marine n-alkanes at this time restricting marine productivity on the continental shelf. The biomarker data for the Early Miocene in DSDP 270 indicates a relative warming in both terrestrial and marine temperatures following the transient Mi-1 glacial expansion, but an overall baseline cooling of climate between Late Oligocene and the Early Miocene in the Ross Sea embayment. Isoprenoid GDGTs are used to reconstruct a Cenozoic subsurface ocean temperature compilation for the Ross Sea, a key source region of ocean deep water. The ocean temperature TEXL86 calibration and BAYSPAR in standard subsurface mode were considered, through comparison with independent microfossil and sedimentological data, the most appropriate for use in this region. Ocean temperatures cool prior to the Eocene/Oligocene transition and remain cool for the rest of the Cenozoic, with the exception of short periods of relative warmth in the Late Oligocene and Mid-Miocene Climate Optimum, and long-term trends broadly mirror that of the foraminiferal δ¹⁸O record from the deep Pacific. The Δ Ring Index is used to assess non-thermal influences on GDGT distributions, and displays a long term shift from more positive to more negative deviations. This correlates with %GDGT-0, and also relates to a declining trend in the Methane Index, which reflect the contribution of methanogenic and methanotrophic archaea. These changes suggest that these archaea contributed more to the archaeal community in the early to mid Cenozoic, potentially indicating a more anoxic depositional environment in the Ross Sea. The Branched to Isoprenoid Tetraether index (BIT) steadily declines over the Cenozoic, reflecting increasingly hyper-arid conditions onshore, with less active glaciofluvial systems, limited soil development and less ice-free land.